Examination of the Enterotoxigenic Escherichia coli Population Structure during Human Infection - Jason W. Sahl (American Society for Microbiology, 2015)
ABSTRACT Enterotoxigenic E. coli (ETEC) can cause severe diarrhea and death in children in developing countries; however, bacterial diversity in natural infection is uncharacterized. In this study, we explored the natural population variation of ETEC from individuals with cholera-like diarrhea. Genomic sequencing and comparative analysis of multiple ETEC isolates from twelve cases of severe diarrhea demonstrated clonal populations in the majority of subjects (10/12). In contrast, a minority of individuals (2/12) yielded phylogenomically divergent ETEC isolates. Detailed examination revealed that isolates also differed in virulence factor content. These genomic data suggest that severe, cholera-like ETEC infections are largely caused by a clonal population of organisms within individual patients. Additionally, the isolation of similar clones from geographically and temporally dispersed cases with similar clinical presentations suggests that some isolates are particularly suited for virulence. The identification of multiple genomically diverse isolates with variable virulence factor profiles from a single subject highlights the dynamic nature of ETEC, as well as a potential weakness in the examination of cultures obtained from a single colony in clinical settings. These findings have implications for vaccine design and provide a framework for the study of population variation in other human pathogens. IMPORTANCE Enterotoxigenic Escherichia coli (ETEC) has been identified as one of the major causes of diarrheal diseases in children as well as travelers. It has been previously appreciated that this pathogenic variant of E. coli is diverse, both at the genomic level, as defined with multilocus sequence typing, and with regard to the presence or absence of virulence factors within clonal groups. Using whole-genome sequencing and comparative analysis, we identified and characterized diverse enterotoxigenic E. coli isolates from individual patients. In 17% of patients, we identified multiple distinct ETEC isolates, each with unique genomic features and in some cases diverse virulence factor profiles. These studies ascertained that any one person may be colonized by multiple pathogenic ETEC isolates, which may impact how we think about the development of vaccines and therapeutics against these organisms.